1981
DOI: 10.3758/bf03326996
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of sodium pentobarbital anesthesia on novelty-induced behaviors

Abstract: Two experiments were performed to evaluate the long-term effects of a single anesthetic dose of sodium pentobarbital on novelty-induced behaviors. In Experiment I, when compared with controls 1 week after injection, pentobarbital-treated rats showed faster step-down latencies in a novelty box and an enhanced plasma corticosterone response to this novel environment. In Experiment 2, when exposed to a novel open field, pentobarbital treated animals showed significantly less ambulation and rearing than did contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The reason for this significant difference between the two restraining methods is not clear and further research will need to determine the long time effect the anesthetic drug that may have on the appetite. It has been reported that the consequences of anaesthesia may be more prolonged than previously presumed (Mcgee et al, 1981) and attenuation of taste neophobia (Rondeau et al, 1975) was reported as among the behavioral changes. Our results further demonstrated the average survival time for the INFECTRA ® -Kit as 20±0.8 while that of the conventionally restrained mice was 22±0.8 while the control group had a survival time more than 30 days.…”
Section: Discussionmentioning
confidence: 98%
“…The reason for this significant difference between the two restraining methods is not clear and further research will need to determine the long time effect the anesthetic drug that may have on the appetite. It has been reported that the consequences of anaesthesia may be more prolonged than previously presumed (Mcgee et al, 1981) and attenuation of taste neophobia (Rondeau et al, 1975) was reported as among the behavioral changes. Our results further demonstrated the average survival time for the INFECTRA ® -Kit as 20±0.8 while that of the conventionally restrained mice was 22±0.8 while the control group had a survival time more than 30 days.…”
Section: Discussionmentioning
confidence: 98%